Soil microbial response to silicate fertilization reduces bioavailable arsenic in contaminated paddies. (August 2021) - Das, Suvendu; Hwang, Hyun Young; Song, Hyeon Ji; Cho, Song Rae; Van Nostrand, Joy D.; Kim, Pil Joo
Abstract: Rice grown in arsenic (As)-contaminated soils will have an elevated As concentration in the edible parts and lower yield due to the stressful growing environment. Silicon fertilizer is a soil amendment that can prevent As bioaccumulation and increase rice yield. This may be due to chemical interactions between silicon and As, but we hypothesized that silicon fertilization would improve soil microbial functions that control the bioavailable As concentration and improve the growing environment for rice in As-contaminated agroecosystems. We tested the hypothesis on two geographically different rice varieties (Indica and Japonica) grown on As spiked soils. Rice grown in pots amended with slag-based silicon fertilizer (silicate fertilizer) at a rate of 2 Mg ha −1 had a significantly lower As concentration in the grain, with 28% less As in the grain of Indica rice and 30% less As in the Japonica rice grain. The rice grain yield was 20–22% greater in these rice varieties. There are several reasons that As uptake declined in the rice grain, including: (i) a reduction in As bioavailability, likely because As was absorbed to amorphous and crystalline iron oxides in the soil and on root Fe-plaque, (ii) an increase in As resistant and arsenite-oxidizing bacteria that likely contribute to the natural attenuation of As in soil, and (iii) an increase in the pore-water silicon concentration that competitively inhibited As uptake by plants. Adding silicate fertilizer improved the general soil fertility by increasing the abundance of microbial functional communities involved in nutrient (carbon, nitrogen, and phosphorus) cycling, nitrogen and carbon fixation, methane consumption, and heavy metals/metalloid detoxification, while decreasing the number of microorganisms involved in methane and nitrous oxide production. We conclude that silicate fertilizer amendments stimulate soil microbial functions that are beneficial for rice growth while controlling As bioavailability, and thus are a potential solution to allow rice production in As-contaminated paddy soils. Graphical abstract: Image 1 Highlights: Silicate fertilizer increased As(III)-oxidizing and As-resistant gene abundance. Silicate fertilizer increased labile C degrading gene, but not recalcitrant C degrading gene abundance. Silicate fertilizer increased C- and N-fixing gene abundance. Silicate fertilizer decreased CH4 producing gene, but increased CH4 consuming gene abundance. Silicate fertilizer decreased As levels in grain, straw and husk, and increased yield.